Actor analysis in sustainable village-based enterprises: Examining the Role of Stakeholders - Irwansyah, M. Rudi; Narmaditya, Bagus Shandy; Vijaya, Diota Prameswari (Jurnal Ekonomi Kuantitatif Terapan; Vol 17 No 2 (2024): Vol. 17, No. 2, Agustus 2024 (pp.156-369), 2024)
Fundamentally, the establishment of village-based enterprises is a mandate of the village law in an effort to encourage or stimulate the wheels of the rural economy and also increase village income sources. The implementation of the mandate of this law makes it important to involve Village-Based Enterprises stakeholders in its management. This study aims to determine the roles and interaction patterns of stakeholders (actors) in the management of village-based enterprises in Bali. The analysis method used in this study is Mactor. Primary data collection was obtained through interviews guided by a questionnaire and direct observation. The research findings indicate that each player, specifically the Village Ministry PDTT, Provincial Government, District Government, Village Government, Village-Based Enterprise Manager, Villagers, and Business Partners, play a crucial role in determining the sustainability of village-based companies. The linkages between actors interact with each other in the management of village-based enterprises and are able to mobilize actors to achieve management goals. All actors agree that village-based enterprises must be developed both in terms of management and institutions. The contribution of the results of this research becomes a recommendation for collaborative planning among stakeholders, so that it becomes a strategic step in sustainable village-based enterprise.